1990
DOI: 10.1111/j.1471-4159.1990.tb03129.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Rises in Plasma Choline Reverse the Negative Arteriovenous Difference of Brain Choline

Abstract: The concentrations of free choline in blood plasma from a peripheral artery and from the transverse sinus, in the CSF, and in total brain homogenate, have been measured in untreated rats and in rats after acute intraperitoneal administration of choline chloride. In untreated rats, the arteriovenous difference of brain choline was related to the arterial choline level. At low arterial blood levels (less than 10 microM) as observed under fasting conditions, the arteriovenous difference was negative (about -2 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 28 publications
1
44
3
Order By: Relevance
“…During the entire experimental period, body weight (F (1,30) ¼ 0·02, P¼ 0·89) and food intake (F (1,14) ¼ 2·92, P¼0·11) were unaffected by dietary B vitamins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the entire experimental period, body weight (F (1,30) ¼ 0·02, P¼ 0·89) and food intake (F (1,14) ¼ 2·92, P¼0·11) were unaffected by dietary B vitamins.…”
Section: Resultsmentioning
confidence: 99%
“…After the supplementation period, analyses of plasma samples revealed that plasma free choline concentration was up to 10 % higher in rats fed the B vitamin-enriched diet than in rats that were continued on the B vitamin-poor diet (F (1,30) ¼ 9·52, P, 0·005; Fig. 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…GPC can be degraded to free choline that is able to cross the BBB (37). Thus, the decrease in brain GPC could result from a compensatory mechanism to replenish blood choline used by the parasite to proliferate, because choline concentration in brain closely parallels choline fluctuations in plasma (38).…”
Section: Discussionmentioning
confidence: 99%
“…In brain, Cho is stored almost completely in a metabolized form (26). Intracellular free Cho concentration is kept low because once Cho is inside the cell, it is rapidly phosphorylated by choline kinase (26,27).…”
Section: Discussionmentioning
confidence: 99%